Memahami Hak dan Kewajiban Negara Berdasarkan Kaidah Fiqih Siyasah - Muh. Zamroni; Liza Elyvia Nur Syayyidah; Lazuardy Arsyad Haris; Indria Fajri; Sefina Wisesa Firda (CV. ITTC INDONESIA, 2025)
This article will discuss the rules of fiqh siyasah related to the rights and obligations of the state accompanied by the basis of the Qur'an and hadith as well as examples of its application in the life of the state. qualitative research type with a normative approach, which is done through (library research). The main focus is to examine and analyze literature, both classical and contemporary, relating to fiqh siyasah and fiqhiyyah rules. The study also applies a normative-theological approach, namely by examining shar'i arguments such as the Qur'an and Hadith, aiming to identify and understand the application of fiqh rules in the practice of siyasah syar'iyyah, Fiqh Rules of Siyasah لَهُمْ مَالَنَا وَعَلَيْهِمْ مَا عَلَيْنَا. Rule of Fiqh Siyasah طَاعَهُ وَلِي الْأَمْرِ وَاجِبَةٌ فِي غَيْرِ مَعْصِيَةٍ. Rule of Fiqh Siyasah لا يُقْبَلُ فِي دَارِ الإِسْلَامِ العُذْرُ بِجَهْلِ الْأَحْكَامِ Taken together, these three rules complement each other in forming an Islamic government system that is just, authoritative, and in favor of the interests of the people. Understanding these rules is not only important for the ruler, but also for the people, in order to create a harmonious synergy between power and obedience, as well as balanced responsibilities and rights under the auspices of Sharia values.